Karakteristik Kimia dan Fisikia Pempek Lenjer dengan Perbandingan Ikan Seluang dan Metode Pemasakan - Dasir, Dasir; Alhanannasir, Alhanannasir; Mukhtaruddin, Mukhtaruddin; Setiawan, Eka A (Universitas Pattimura, 2023)
The scarcity of belida fish and snakehead fish as raw materials for pempek is due to the not-yet-optimal cultivation efforts being carried out, and belida fish are protected or prohibited from being caught, causing the price of these fish more expensive. Pempek entrepreneurs replace it with sea fish such as mackerel, parang-parang fish, and other types of sea fish, but the taste and aroma of the pempek produced are slightly fishy. This problem causes the need to use alternative freshwater fish, including seluang fish. The method of solving the problem is to research making pempek with a ratio of seluang fish consisting of (S1) = 40% seluang fish: 60% tapioca flour, (S2) = 50% seluang fish: 50% tapioca flour, (S3) = seluang fish 60%: 40% tapioca flour with the cooking method (M1) = steaming method and M2 = boiling method. The results of research on the average pempek protein content ranged from3.23% to 8.51%, fat content from 2.10% to 4.44%, calcium levels from 157.33 mg/10 g to 224.00 mg/100 g, and the average elasticity from 0.4 gF to 2.10 gF. The conclusion of the research results showed that pempek lenjer with a ratio of seluang S3 (60% seluang fish with 40% tapioca flour) and cooking method M1 (steaming) had a very significant effect on protein content, fat content, calcium levels, and elasticity. The highest protein, fat, and calcium content, respectively 8.51%, 4.44%, and 224 mg/100 g, were found in S3M1 (60% seluang fish with 40% tapioca flour and boiling method). In comparison, the highest chewiness was in S1M1 (40% seluang fish with 60% tapioca flour and steaming).